Fasiliti di Stesen Monorel: Cabaran kepada Orang Kelainan Upaya - Mohamad Surani, Huzailina; Md. Yassin, Azlina; Masram, Haidaliza (Research in Management of Technology and Business, 2020)
KL Monorail is a modern transportation service that provides transportation links throughout the city of Kuala Lumpur. Its development is to provide convenience and perfection to Malaysians in facing survival regardless of the social level of life. However, the lack of facilities provided at the Kuala Lumpur monorail station has caused disaster especially after the country was shocked by several accidents at the station and even more unfortunate when the accident had involved people with disabilities (OKU). Therefore, this study was conducted with the objective to identify the facilities provided for the disabled people (OKU) at the Kuala Lumpur Monorail Station, and to examine the challenges faced by the disabled people while using the facilities provided at the Monorail Station. The findings of the study were obtained through the implementation of qualitative methods by adapting observational and interview approaches. The respondents involved in this study consist of five people with disabilities who are users of monorail services. The findings of the study show that the facilities provided at the Kuala Lumpur Monorail Station are adequate for the needs of users but need to be upgraded for the convenience of users with disabilities. Hopefully, the findings of this study will be benefitted to the management of the Kuala Lumpur Monorail for making improvements in the future.